Legal Protection for Notarists in The Providing of Working Capital Credit by Bank (Study of The Decision of Mahkamah Agung Number 65 K/Pdt/2020) - Vianney, Janice; Nurdin, Aad Rusyad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Banks are business entities that collect funds from the public in the form of credit or other forms in order to improve the standard of living of many people. Based on the Banking Law, credit is "the provision of money or similar bills based on a loan agreement (lending and borrowing) between the bank and another party in which case the borrower is obliged to pay off the debt after a certain period of time with a predetermined amount of interest." In credit agreements, the role of a Notary is required to have the authority to make authentic deeds. In this research the problems raised are: 1. What are the roles and responsibilities of a Notary in a Bank Credit Agreement? 2. What is the legal protection for Notaries in granting Working Capital Credit by Banks based on Supreme Court Decision Number 65 K/Pdt.2020? The form of this research is doctrinal research with data collection through literature study. Based on this research, it can be concluded that the Notary has the authority to make authentic deeds as evidence that has perfect evidential power and is also burdened with responsibility in carrying out his position. The presence of the Notary Honorary Council aims to provide guidance and protection for Notaries in carrying out their positions.